Answer:
a) (x-2)² = 25
b) 7 and -3
Explanation:
Given the expression 24 = x^2 - 4x + 3
Rewrite
x^2 - 4x + 3 - 24 = 0
x^2 - 4x - 21 = 0
Add 21 to both sides
x^2 - 4x - 21 + 21 = 0 + 21
x^2 - 4x = 21
Add the square of the half of coefficient of x to both sides
constant to add = (-4/2)² = (-2)²
x^2 - 4x + (-2)² = 21 + (-2)²
(x-2)² = 21 + 4
(x-2)² = 25
Hence the rewritten form of the equation is (x-2)² = 25
Calculate the value of x
(x-2)² = 25
Square root both sides
√(x-2)² = ±√25
x - 2 = ±5
x= ±5 + 2
x = 5 +2 and-5+2
x = 7 and -3
Hence the solutions to the equation are 7 and -3